Cetovinodanakāvyam of Dājī Jyotirvid - Dāji Jyotirvid, 1800-1865.; Wakankar, S. Y.; Joshi, P. H.; Maharaja Sayajirao University of Baroda (Vadodara : Oriental Institute, M.S. University of Baroda : Copies can be had from University Publications Sales Unit, M.S. University of Baroda Press (Sadhana Press)m, 1991)
Description of various pilgrimages in India, in verse form.
Includes index.
"Copies: 250."
In Sanskrit; prefatory matter in English.
Mode of access: Internet.
Keywords: Hindu pilgrims and pilgrimages